Polyfluorenes - Scherf, Ullrich. (Springer, 2017)
A.C. Grimsdale, K. Müllen: Bridged Polyphenylenes -- From Polyfluorenes to Ladder Polymers -- S.-A. Chen, H.-H. Lu, C.-W. Huang: Polyfluorenes for Device Applications -- W.W.H. Wong, A.B. Holmes: Poly(dibenzosilole)s -- P.-L.T. Boudreault, N. Blouin, M. Leclerc: Poly(2,7-Carbazole)s and Related Polymers -- S.-J. Liu, Y. Zhao, B.-X. Mi, W. Huang: Polyfluorenes with On-Chain Metal Centers -- J.U. Wallace, S.H. Chen: Fluorene-Based Conjugated Oligomers for Organic Photonics and Electronics -- A. Monkman, C. Rothe, S. King, F. Dias: Polyfluorene Photophysics -- M. Knaapila, M.J. Winokur: Structure and Morphology of Polyfluorenes in Solutions and the Solid State -- S. Kappaun, C. Slugovc, E.J.W. List: Optically Active Chemical Defects in Polyfluorene-type Polymers and Devices -- E. Da Como, K. Becker, J.M. Lupton: Single Molecule Spectroscopy of Polyfluorenes.-